ANALYSIS OF STRESS-TEST YOUR STRATEGY AND AMBIDEXTROUS STRATEGY FOR COUNTIONAL INNOVATION - Mimi Kurnia Nengsih; Meiffa Herfianti (Universitas Muhammadiyah Bengkulu, 2022)
Competition in a global world requires every industry to innovate to survive in a constantly changing environment. Organizations are required to always be innovative, but to be innovative is not enough to be creative alone, but also requires ideas that can be applied to create value for the organization. Fajarwonk is one of the SMEs that uses hanging leather as a product that is worth selling, such as bags and regional souvenirs that are exclusive to Bengkulu City. This research aims to identify strategies that have been used by Fajarwonk to see the weaknesses and strengths of the strategies that have been carried out by Fajarwonk in marketing its products and continuous innovation. This study uses a qualitative approach by collecting data through interviews with businesspeople and Fajarwonk employees and using the Stress-Test Your Strategy, and Ambidextrous Strategy approaches. Research result Fajarwonk has main customers, namely the middle and upper-middle class, Fajarwonk establishes current core values ​​by prioritizing the interests of customers to increase sales of quality products, to maintain consumer confidence in product quality Fajarwonk provides training and special skills and responsibilities to each employee and provides flexibility to employees who have creative ideas in product design.